INTERPRETASI E-LEARNING SEBAGAI SUPPORT MEDIA UNTUK PEMBELAJARAN BAHASA MANDARIN BAGI SISWA SEKOLAH DASAR - Hari, Yulius; Aspali, Darmanto; Hermawan, Budi (Institute of Research and Community Outreach - Petra Christian University, 2014)
Nowadays, many schools are teaching the Chinese Language as curriculum, including elementary school. While the major problems in Chinese language learning is a form of pronunciation or intonation that much different from the Indonesia language who does not pay attention to the tone. In the Chinese language curriculum students are expected to be able to listen, to pronounce, to read and to write. Furthermore, learning arithmetic subject in Chinese language is quite difficult, because besides being able to pronounce the numbers correctly, the student should be able to count it. Hence the limitations of print media is not able to accommodate learning in listening, especially pronunciation or intonation correctly and also the writing. This led to the emergence of the spatian contiguity between text books with information on what is perceived by the learner. This study attempts to bridge these limitations by accommodating a media in web-based learning that also train the ability to listen and write, so that the spatial distance between the information in the book with a learner can be reduced . The results of this study are expected to provide a new alternative as a model for Chinese language learning, especially in Indonesia.